Parametric analyses of anxiety in zebrafish scototaxis - Maximino, Caio; de Brito, Thiago Marques; Colmanetti, Rafael [UNESP]; Assis Pontes, Alvaro Antonio [UNESP]; de Castro, Henrique Meira [UNESP]; Tavares de Lacerda, Renata Inah [UNESP]; Morato, Silvio; Gouveia, Amauri (Elsevier B.V., 2010)
Scototaxis, the preference for dark environments in detriment of bright ones, is an index of anxiety in zebrafish. In this work, we analyzed avoidance of the white compartment by analysis of the spatiotemporal pattern of exploratory behavior (time spent in the white compartment of the apparatus and shuttle frequency between compartments) and swimming ethogram (thigmotaxis, freezing and burst swimming in the white compartment) in four experiments. In Experiment 1, we demonstrate that spatiotemporal measures of white avoidance and locomotion do not habituate during a single 15-min session. In Experiments 2 and 3, we demonstrate that locomotor activity habituates to repeated exposures to the apparatus, regardless of whether inter-trial interval is 15-min or 24-h; however, no habituation of white avoidance was observed in either experiment. In Experiment 4, we confined animals for three 15-min sessions in the white compartment prior to recording spatiotemporal and ethogram measures in a standard preference test. After these forced exposures, white avoidance and locomotor activity showed no differences in relation to non-confined animals, but burst swimming, thigmotaxis and freezing in the white compartment were all decreased. These results suggest that neither avoidance of the white compartment nor approach to the black compartment account for the behavior of zebrafish in the scototaxis test. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Zebrafish; Fear; Anxiety; Behavior; Avoidance; Scototaxis; Motivation; Drive